EMT 억제를 통한 멜리틴의 폐암세포 이동 및 침투 억제 효과 - 조현지(Hyun-Ji Cho); 정윤정(Yun-Jeong Jeong); 김문현(Mun-Hyeon Kim); 정일경(Il-Kyung Chung); 강동욱(Dong Wook Kang); 장영채(Young-Chae Chang) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
Melittin is the main component of apitoxin (bee venom) that has been reported to have anti-inflammatory and anti-cancer effects. Herein, we demonstrated that inhibition of epithelial-mesenchymal transition (EMT) by melittin causes suppression of cancer cell migration and invasion. Melittin significantly suppressed the epidermal growth factor (EGF)- induced cell migration and invasion in lung cancer cells. Moreover, melittin up-regulated the expression of epithelial marker protein, E-cadherin, and down-regulated the expression of EMT related proteins, vimentin and fibronectin. Mechanistic studies revealed that melittin markedly suppressed the expression of EMT mediated transcription factors, ZEB2, Slug, and Snail. The EGF-induced phosphorylation of AKT, mTOR, P70S6K, and 4EBP1 was also inhibited by melittin, but not that of ERK and JNK. Therefore, the inhibitory effect of melittin on migration and invasion of lung cancer cells may be associated with the inhibition of EMT via blocking of the AKT-mTOR-P70S6K-4EBP1 pathway.